Principal's Leadership Style: Impact on Student Motivation and Teacher Performance - Awaludin Awaludin; Fatmawati Fatmawati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the impact of principal leadership styles on student motivation and teacher performance in public secondary schools in Medan City. Using a quantitative approach with a survey method, this study involved 290 teachers and 350 students selected through stratified random sampling. Data were collected using a Likert scale questionnaire and analyzed using multiple linear regression through SPSS software. Student motivation was rated very high, representing strong engagement and clear academic goals, while teacher performance was classified as very good, especially in planning and implementing learning. These results underscore the important role of inspirational, communicative, and participatory leadership in improving educational outcomes. This study suggests that principals who adopt these styles create a supportive climate that enhances student enthusiasm and teacher professionalism. These findings have significant power to develop leadership training programs to improve principal capacity, which ultimately improves the quality of education. This study highlights the need for adaptive leadership strategies tailored to the diverse school contexts in Medan, providing actionable insights for education policymakers and school administrators to foster effective learning environments.